(untitled) (American Journal of Islam and Society, 1986)
I met Dr. Lois Lamya al Faruqi last March, while I was giving a lecture on Arabic calligraphy at the University of Pennsylvania in Philadelphia. I had corresponded with her previously and had been impressed by her graciousness and her insight into the complex field of Islamic art. Now, here she and her husband were, and I was pleased to have these bright lights of the Muslim community in my audience. At the end of my remarks, someone asked the inevitable question, "What is the significance, the symbolism of the designs used to highlight a calligraphic piece?" I replied that, while some Islamic designs have their origins in the material world, they become abstracted and stylized but do not take on additional symbolic meaning. In other words, Islamic art, at its best, does not depend on visual symbols as clues to its meaning. A flower Wing remains a flower drawing, no matter how abstract it becomes. Dr. Faruqi’s was interested in my interpretation and, I think somewhat amused. As she left that evening, I saw a definite twinkle in her eye, and I felt I had found a congenial colleague. Two weeks later, I received an autographed copy of Islam and Art from her. I never saw her again. I am pleased to have this opportunity to review this volume, Dr. Faruqi’s last published work. Let me make my own position clear: I am neither an academician nor a genuine scholar of Islamic art. Rather, I approach the subject as a practitioner; therefore, my interest in Islamic art-and in this book- is at once personal, practical, and professional. Why do the arts of the Muslim peoples-and by arts, I include graphic arts, architecture, crafts, and music -develop with such obvious consistency from people to people, and in such a straight line from their inception to the present? This question has baffled scholars for at least a century. Dr. Faruqi’s insight guides the reader in the direction of a true answer, yet it is an answer each of us must experience for ourselves, through study and contemplation. In short, Dr. Faruqi’s answer to this central question is that the arts of the Muslim peoples did not develop by chance, but rather, as an attempt to express by various media the Quranic doctrine of tawhid, the immense ...